Knowledge, attitude and prescriptional practice about fixed dose combinations among medical practitioners in tertiary care hospital - Ravichandran, Aravind; Balamurugan, Jayapriya; Shankareshwari, .; Sekar, Ramalingam (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Fixed dose combination (FDC) are currently most prescribed and misused drug forms. Although fixed dose combinations are clinically better than single dosage forms, improper prescription and large amounts of irrational FDC flooding leads to unwanted financial burden and increased resistance. Therefore a study was carried out to know about the existing scenario about Knowledge Attitude and Practice of Fixed dose combinations among the resident doctors and devise some suggestions for improving the rationality. The objective of the study was to evaluate the knowledge, attitude and prescriptional practice regarding fixed dose combinations among resident doctors working in a Government Theni medical college, Theni. Methods: A cross-sectional descriptive study involving 100 resident doctors was conducted using a pre validated questionnaire containing 21 questions to evaluate the knowledge and prescriptional practice of Fixed Dose Combination among the study participants. Results: Ninety-five percent of the study participants were aware of the Fixed dose combination. Increased compliance and synergistic drug effect are the commonly cited advantages, whereas difficulty in dose adjustment and increased side effects were the commonly told disadvantages. Only 13% of the participants could name a single banned drug. Antibiotics (63%), NSAIDS (18%) were the commonly prescribed FDCs among study participants. Internet (58%), followed by textbook (42%) and colleagues (37%) were the common sources of knowledge about FDCs. Increasing awareness about Essential Medicines List (63%), regular CME (55%) and prior notification (50%) are some of the measures recommended by study participants to improve the awareness. Conclusions: Although the participants are aware of basic knowledge of fixed dose combinations are acceptable, prescribing FDC them often, many of the study participants lack knowledge about the rationality of these drugs. From our study, conducting regular CME’s about new Fixed dose combinations in the medical colleges and periodic notification of FDC’s are some of the suggested approaches to improve the rationality of prescription. Since Internet is listed as the most common source of knowledge about FDC, information about FDC can be sent through mails, text messages, which will play a part in improving the rationality of FDC.